How Trade Credits Foster International Trade - Katharina Eck; Martina Engemann; Monika Schnitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
Internationally active firms rely intensively on trade credits even though they are considered particularly expensive. This phenomenon has been little explored so far. Our theoretical analysis shows that trade credits can alleviate financial constraints arising from asymmetric information because they serve as a quality signal and reduce the uncertainty related to international transactions. We use unique survey data on German enterprises to test the effect of the use of trade credits on firms' exporting and importing behavior, both at the extensive and intensive margins. Our results support the assertion that trade credits have a positive impact on firms' exporting and importing activities.
urn:nbn:de:bvb:19-epub-13175-1
Keywords: F10; G30; 330; trade credits; international trade; financial constraints; export; import; BEEPS; Lieferantenkredit; Außenhandelssektor; Liquiditätsbeschränkung; Signalling; Schätzung; Deutschland